Visualizing temporal dynamics and research trends of macrophage-related diabetes studies between 2000 and 2022: a bibliometric analysis - Wang, Sicheng; Zhang, Lili; Jin, Zishan; Wang, Yayun; Zhang, Boxun; Zhao, Linhua (Frontiers in Immunology, 2023)
Background: Macrophages are considered an essential source of inflammatory cytokines, which play a pivotal role in the development of diabetes and its sequent complications. Therefore, a better understanding of the intersection between the development of diabetes and macrophage is of massive importance. Objectives: In this study, we performed an informative bibliometric analysis to enlighten relevant research directions, provide valuable metrics for financing decisions, and help academics to gain a quick understanding of the current macrophage-related diabetes studies knowledge domain. Methods: The Web of Science Core Collection database was used for literature retrieval and dataset export. Bibliometrix R-package was performed to conduct raw data screening, calculating, and visualizing. Results: Between 2000 and 2022, the annual publication and citation trends steadily increased. Wu Yonggui was the scholar with the most published papers in this field. The institute with the highest number of published papers was the University of Michigan. The most robust academic collaboration was observed between China and the United States of America. Diabetologia was the journal that published the most relevant publications. The author’s keywords with the highest occurrences were “inflammation”, “diabetic nephropathy”, and “obesity”. In addition, “Macrophage polarization” was the current motor topic with potential research prospects. Conclusions: These comprehensive and visualized bibliometric results summarized the significant findings in macrophage-related diabetes studies over the past 20 years. It would enlighten subsequent studies from a macro viewpoint and is also expected to strengthen investment policies in future macrophage-related diabetes studies.